Experimental study on combustion behavior and fire extinguishing of lithium iron phosphate battery. (August 2020) - Meng, Xiangdong; Yang, Kai; Zhang, Mingjie; Gao, Fei; Liu, Yujun; Duan, Qiangling; Wang, Qingsong
Highlights: The combustion behavior of lithium iron phosphate battery was investigated. The gas toxicity of lithium iron phosphate battery combustion was studied. The heat release rate of lithium iron phosphate battery during combustion was measured. The fire extinguishing effect of dry powder on lithium iron phosphate battery was analyzed. Abstract: The fire hazard resulting from the thermal runaway (TR) of lithium-ion batteries (LIBs) poses a great threat, but it is still a challenge to extinguish LIB fires effectively and promptly. In this work, an experimental platform is constructed to investigate the combustion behavior and toxicity of lithium iron phosphate battery with different states of charge (SOCs) and suppression efficiency of dry powder in LIB fires. The results indicate that the fully-charged battery undergoes TR when its surface temperature reaches at 166.8 °C and releases combustible gases such as CO, CO2 and HF. The LIB has the greater thermal risk and toxicity with the higher SOC value. The maximum heat release rate reaches 12.1 kW and the normalized HRR value is 6.2 MW m −2 . It is found that dry powder could extinguish LIB fires under the given appreciate conditions. The suppression and cooling effects become better with the shorter spraying distance and the longer spraying time, but the effects are not affected by the spraying angle. However, this agent couldn't prevent the exothermic reaction inside the battery, thus it has a limited cooling effect only on the parts of the agent contacted.